1990
DOI: 10.1039/ft9908603279
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reactivity of peroxyl and sulphoxyl radicals from measurement of oxygen-17 hyperfine couplings: relationship with taft substituent parameters

Abstract: Radicals from Relationship withA series of peroxyl radicals (ROO') with substituent groups of varying electron withdrawing power have been investigated using electron paramagnetic resonance spectroscopy. Sixteen carbon-based radicals have been produced, identified and reacted with ' '0-labelled molecular oxygen to produce the corresponding peroxyl radical. Carboncentred radical precursors include alkyl, aromatic, halocarbon, lipid and alcohol radicals. The oxygen-17 hyperfine couplings are shown to monitor clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 23 publications
4
46
2
Order By: Relevance
“…In the latter case, owing to the unequal distribution of spin in the -OO • fragment, two superimposed sextets should appear in the spectrum (due to -O 17 O • and -17 OO • ), as widely reported in the literature [30][31][32]. If O 2 -reacted with CH 3 CN at 210 K forming such a peroxy entity (i.e.…”
Section: Resultsmentioning
confidence: 86%
“…In the latter case, owing to the unequal distribution of spin in the -OO • fragment, two superimposed sextets should appear in the spectrum (due to -O 17 O • and -17 OO • ), as widely reported in the literature [30][31][32]. If O 2 -reacted with CH 3 CN at 210 K forming such a peroxy entity (i.e.…”
Section: Resultsmentioning
confidence: 86%
“…Using experimental EPR data from studies of peroxide radicals, ROO (Sevilla et al, 1990;Broze et al, 1967) and the empirical McConnell-Strathdee relations (McConnell and Strathdee, 1959, and references therein), the Axx andAyy components and the spin density were then derived by Hoganson for the tyrosyl oxygen. The estimated values for the xx and yy components of the hyperfine tensor are quite low, however (+4.9 G, compared with our calculated values of + 13 G), as is the experimental oxygen spin density (exp.…”
Section: Resultsmentioning
confidence: 99%
“…1989, Sevilla et al . 1990a) and that the RS0 2 00' radical is likely a highly reactive hydrogen abstracting agent (Sevilla et al . 1990b) .…”
Section: Discussionmentioning
confidence: 96%
“…However, RSOO' is not considered to be a good hydrogen abstractor (Sevilla et al 1990b) although one report suggests that it is an effective one-electron oxidant (Tamba et al 1986) . ESR work has shown that RSOO' is involved in a cyclic reaction sequence (reaction 6) which results in a highly reactive intermediate RS0 200' (Sevilla et al 1988(Sevilla et al , 1990a(Sevilla et al , 1990b .…”
Section: Rs' +Rsh Rssr' -+ H +mentioning
confidence: 98%
See 1 more Smart Citation